Tractography Neuroanatomical Study of Dyslexia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Catholic University of Leuven, Belgium used diffusion tensor imaging tractography, a structural MRI technique, to assess the integrity of white matter tracts involved in reading.